Australia : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Australia. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2021)
Strong health and economic policies allowed for quick economic recovery from initial COVID-19-related lockdowns in 2020. Renewed outbreaks and lockdowns have created setbacks since mid-2021, with disproportionate impacts on some regions, sectors, and workers. Accommodative macroeconomic policies have been instrumental in cushioning the economic impact.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Australia